Whey protein: How does it affect the increase in muscle mass of untrained athletes post weight training? - Yendrizal; Pratama, Angga Okta; Yenes, Ronni; Irawan, Roma; Ramadhan, Riang Hari; Maidarman, Maidarman (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Weight training is a type of exercise that can provide many benefits for the body. Apart from exercise programs, the nutritional intake consumed also influences the success of building muscle through weight training. Protein is the main element that influences muscle growth and development after doing weight training. This experimental study used a pretest-posttest control group design to examine the effect of whey protein on muscle hypertrophy. It involved 60 male student athletes from Padang, Indonesia, aged 18-25 with a BMI of 25-29, physically healthy, and willing to follow research guidelines. The experimental group (n = 30) was given whey protein 30 minutes after weight training as much as ± 45 grams while the control group (n = 30) was only given mineral water after weight training. Muscle hypertrophy was measured using a measuring tape and skinfold calipers. Muscle circumference was calculated using the formula: MTC − (3.14 × TSF), where MTC is the muscle circumference and TSF is the triceps skinfold thickness. The results indicated that the group consuming whey protein experienced a significantly greater increase in muscle circumference compared to the control group (p<0.05). Based on research findings, planned and structured weight training combined with whey protein supplementation can maximize muscle hypertrophy compared to training without whey protein.